STRATEGI INDUSTRI KECIL MENENGAH DI MASA PANDEMI COVID-19 DALAM MENINGKATKAN EKSISTENSI USAHA MELALUI MEMBANGUN MITRA SEBAGAI VARIABEL INTERVENING (SURVEY PADA INDUSTRI PAKAIAN JADI DI KOTA PEKANBARU) - Ulfa Ulfa; Hendriani Susi; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The Covid-19 pandemic has not only resulted in a public health crisis but has had a sugnificant impact on all aspects of life. Small and medium industry is one of the sectors affected by the Covid-19 pandemic. This sector has experienced a significant impact. The condition of small and medium industries in the midst of a pandemic contineus to experience a decline in capacity, ranging from production capacity to a decrease in income. The existence of small and medium industries in Indonesia is very important because they tend to be better at absorbing a productive workforce, can achieve productivity through investment and technological change, and have an advantage in terms of flexibility. Facing a pandemic, small and medium industry players are required to change their way of thingking, mental attitude, and strategy to maintain their existence in this mass pandemic. The Covid-19 pandemic also requires small and medium industry players to equip themselves with new skills and innovations, which is no less important to prepare business sustainability measures so that they can survive or improve their business existence. During the pandemic, most of the small and medium industry players tried to survive by carrying out a number of strategies. This study aims to determine the strategies of small and medium apparel industry players in the city of Pekanbaru in maintaining the existence of their business, whether by using an online marketing system, product innovation, and building partners can increase the existence of the apparel industry business in the city of Pekanbaru. Primary and secondary, with a total of 78 business actors as respondents. Data collection using queationnaires and direct interviews. The results of this study indicate that the strategy of online marketing systems and building partners to be able to maintain business existence has not been implemented by business actors, business actors are more innovating their product to survive in this covid-19 pandemic era.Keywords: Online Marketing System, Product Innovation, Building Partners, Business Existence, and Small and Medium Industries